Retroviral transduction of human periodontal cells with a temperature-sensitive SV40 large T antigen - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The periodontal ligament (PDL) is considered to contain subpopulations of cells responsible for the development, repair and regeneration of the periodontium. Cell cultures have been used as model systems in order to understand the complex cellular and biochemical events underlying these processes, In order to obtain long-term cultures of these cells that can be cloned and characterized, primary cultures of PDL and gingival cells were infected with an amphotropic retroviral construct encoding a temperature-sensitive SV40 large T antigen (tsT). After selection for drug resistance, the cells expressed the T antigen and proliferated at 34 degrees C for more than 40 passages. However, when the T antigen was inactivated by incubation at 39 degrees C, the cultures became growth-arrested and the granularity of the cells increased, possibly as a result of differentiation. Reverse transcribed-polymerase chain reaction and flow cytometry showed that the tsT-transduced cells expressed a number of soft and hard connective-tissue antigens, including osteocalcin, osteonectin, osteopontin, collagen type I and alkaline phosphatase. Moreover, incubation of the transduced PDL cells at 39 degrees C was found to upregulate the expression of osteocalcin, osteopontin and collagen type I, but downregulate osteonectin. At this temperature, the presence of the dexamethasone downregulated type I collagen, while vitamin D-3 had no effect on the expression of any of the antigens examined. Under all culture conditions, antigen expression was far higher in the transduced PDL cells than the gingival cells. The findings thus show that growth of the tsT-transduced PDL and gingival cells is temperature-dependent and that the presence of the T antigen increases their lifespan but does not ablate the expression of certain of their characteristic phenotypic and functional features. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: periodontal cells; SV40 T antigen; HUMAN GINGIVAL FIBROBLASTS; OSTEOBLAST-LIKE CELLS; LARGE TUMOR-ANTIGEN; LIGAMENT CELLS; ALKALINE-PHOSPHATASE; GENE-EXPRESSION; IN-VITRO; FLOW-CYTOMETRY; INVITRO; LINE